Assessment of Immunological, Skeletal, and Thyroid Function Abnormalities in Paediatric Morphoea - Vibhu Mendiratta; Anuja Yadav; Amit K. Meena; Suvarna Samudrala; Ritu Singh; Vishal Parmar (Indian Journal of Dermatology)
Background: Morphoea is a sclerosing disorder of skin and subcutaneous tissue. Paediatric morphoea shows increased prevalence of various auto-immune diseases, bone deformities, and systemic abnormalities. There is paucity of studies on various immunological, skeletal, and thyroid function abnormalities in paediatric morphoea. Aims and Objectives: To describe immunological, skeletal, and thyroid function abnormalities present in paediatric morphoea patients. Materials and Methods: This cross-sectional study was conducted from January 2021 to March 2023 in the Dermatology outpatient department in a tertiary care hospital. All paediatric morphoea patients were included in this study. All were subjected to detailed history, clinical examination, and investigations including complete blood count, serum IgE, anti-nuclear antibody, thyroid function tests, anti-thyroid peroxidase antibodies, and radiological investigations. Results: A total of 42 children were recruited, out of which 61.90% were females and 38.09% were males. The majority were in the age group of 4–8 years. The most common type of morphoea was encoup de sabre. Anaemia was present in 14.28% patients. Serum IgE levels were raised in 33.33% patients. Thyroid stimulating hormone was raised in 11.9% patients. 33.33% had raised anti-thyroid peroxidase levels. Anti-nuclear antibody titres and rheumatoid factor were raised in 7.14% and 4.76% patients, respectively. Magnetic resonance imaging brain revealed abnormalities in three patients as hyper-intensities in subcortical white matter. Conclusion: Morphoea in children can be associated with varied immunological, osteoarticular, and neurological abnormalities. This study highlights the multi-system involvement in morphoea and the need for larger data and well-designed therapeutic trials for generating evidence-based treatment of this potentially disfiguring disease.